Ultrasound characterization of superficial lymph nodes in HIV patients with Talaromyces marneffei infection - Pan, Lin; Shao, Huaguo (Frontiers in Medicine, 2023)
Objectives This study aimed at exploring the ultrasound characteristics of superficial lymph nodes (LNs) in HIV patients with Talaromyces marneffei infection to provide assistance and understanding for diagnosis and therapy. Methods A retrospective analysis was conducted on 26 patients with confirmed HIV and T.marneffei coinfection. These patients underwent ultrasound examination and ultrasound-guided puncture biopsies at our hospital from March 2015 to March 2023. Results In all 26 patients, lymphadenectasis was observed. Among the 21 cases (80.76%), LNs showed a diffusely hyperechoic appearance with a tulle-like change, and 6 cases (23.07%) showed liquefaction. When the hila were present or thinned, the blood flow signals were primarily hilar, whether rich or poor, and when the hila were absent, the blood flow signals were peripheral or poor. The axillary LN long-to-short diameter (L/S) ratios exhibited a significant positive correlation with CD4+T cell counts (r = 0.8214, p = 0.0341). Patients with retroperitoneal lymphadenectasis showed decreased NK cell counts (p = 0.03). Conclusion In summary, the T.marneffei infection of LNs in HIV patients often manifests with superficial LN enlargement, mostly affecting the cervical LNs. The T.marneffei-infected LNs exhibit several characteristics such as echogenicity, hilum, and blood flow signal. Furthermore, there might be associations between lymphocyte subsets and enlarged superficial LNs. Ultrasound examinations should be paid attention to if patients have superficial LN enlargement, and the diagnosis of the T.marneffei infection is considered.